About the Transformation of Accountancy under the Influence of Information Technology - R. P. Bulyga (Учёт. Анализ. Аудит)
The article presents the results of the research conducted by the Accounting, Analysis and Audit Department of the Financial University under the Government of the Russian Federation in order to answer the following question: to what extent the functions implemented now by a human are subject to “information technology factor” and can be fulfilled and further replaced by computers? The subject of the research is the labor functions stated in the basic professional standards of the Russian Federation for accountants and auditors. On the basis of the research the authors conclude that the influence of information technology on the accounting and audit functions will result in intellectualization of the profession and the use of larger data arrays compiled by IT tools and programs to make professional judgment.